Modification of Problem Based Learning and Team Based Learning Method In Group and Community Intervention Course - Rakhmaditya Noorrizki; Mochammad Sa’id; Angga Yuni Mantara (Universitas Cokroaminoto Palopo, 2023)
Group and community intervention is applied course of social psychology. Several studies show the use of modified problem-based learning and team-based learning methods is effective to achieve the objectives of applied courses. This study aimed to see the effectivity of applying modified problem-based learning and team-based learning methods on group and community intervention course material in increasing students’ understanding. One-group pre test – post test experimental research design was used to conduct this study. The subjects were students who take group and community intervention courses. Data is taken from quiz score given before and after the intervention. The results of the analysis using one-way ANOVA repeated measure with sphericity assumed shows the average student understanding statistically increased between the time of measurement F (2,32) = 127,067, p .000<.005. Thus, it is proven that students' understanding of student subject matter significantly increased.